A study on the necessity for a formal legal framework on embryonic stem cell research in Malaysia / Norsyazwani Suidan ...[et al.] - Suidan, Norsyazwani; Safuan, Noor Adlina Safina; Mohamad, Rosmasafrina; Meor Mohd Nazir, Siti Noratiqah (2011)
Stem cell research, especially on embryonic stem cell research has always raised issues not only on its ethicality in performing the research, but also on the technique used and the usage of the abstracted cell. Apart from that, the question on the usage of embryonic stem cell has arisen in relation to the religious perspectives and the spectrum of morality throughout our country. The other controversial issues are the status of human embryonic stem cell that has been used in the research and its rights in order to live without being aborted for the sake of the research. In Malaysia, there is a regulation that regulates human rights, namely Malaysian Federal Constitution. However, questions always arise whether this regulation covers the right of embryos and foetus that will be used in the embryonic stem cell research. In response to this problem, we propose to carry out a study on the necessity of a formal legal framework on embryonic stem cell research in Malaysia. The objectives of this study are to identify the policies and guidelines' and the current problem surrounding the stem cell research in Malaysia. Besides that, this study is also done, to propose any recommendations in order to improve the stem cell research in our country so that it will beneficial to those who wish to know the legal status of embryonic stem cell research.